2021
DOI: 10.3390/diagnostics11071202
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy Is a Promising Tool for Genetic Testing in Idiopathic Pulmonary Fibrosis

Abstract: Liquid biopsy, which allows the isolation of circulating cell-free (ccf) DNA from blood, is an emerging noninvasive tool widely used in oncology for diagnostic and prognosis purposes. Previous data have shown that serum cfDNA discriminates idiopathic pulmonary fibrosis (IPF) from other interstitial lung diseases. Our study aimed to measure plasma levels of ccfDNA in 59 consecutive therapy-naive and clinically stable IPF patients. The single nucleotide polymorphism (SNP) of the MUC5B gene promoter (rs35705950),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Indeed, the TGF-β that is a chemotactic factor for monocytes and macrophages, and triggers in these cell populations the release of PDGF, IL-1β, basic FGF (bFGF), and TNF-α. To this purpose, an upregulation of the TGF-β expression level has been observed both in AECs and macrophages from the lung tissues of IPF patients [23] as well as in IPF induced in vivo model named the bleomycin mouse model [24]. Indeed, to this purpose the alveolar macrophages play an important role in both IPF and lung cancer progression as highlighted in the work of Jovanovic et al [145], who found positive membrane PD-L1 expression in alveolar macrophages of IPF lung tissue samples in 9 samples out of 12.…”
Section: The Onset and Progression Of Ipf: The Leading Role Of Tgf-β1mentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the TGF-β that is a chemotactic factor for monocytes and macrophages, and triggers in these cell populations the release of PDGF, IL-1β, basic FGF (bFGF), and TNF-α. To this purpose, an upregulation of the TGF-β expression level has been observed both in AECs and macrophages from the lung tissues of IPF patients [23] as well as in IPF induced in vivo model named the bleomycin mouse model [24]. Indeed, to this purpose the alveolar macrophages play an important role in both IPF and lung cancer progression as highlighted in the work of Jovanovic et al [145], who found positive membrane PD-L1 expression in alveolar macrophages of IPF lung tissue samples in 9 samples out of 12.…”
Section: The Onset and Progression Of Ipf: The Leading Role Of Tgf-β1mentioning
confidence: 99%
“…Non-fibrillar collagens (such as collagen VI) have been reported to stimulate myofibroblast trans-differentiation, both in vitro and in vivo [201]. Moreover, the deposition of pericellular hyaluronan may also facilitate and maintain myofibroblast trans-differentiation in response to TGF-β [194], while an independent activation of CD44 signalling by hyaluronan may accentuate the TGF-β/SMAD signalling cascade [24]. Myofibroblasts are also able to modify the biological and mechanical properties of ECM through the secretion of MMPs and tissue inhibitors of metalloproteinases (TIMPs) [202].…”
Section: The Key Role Of Myofibroblasts In Fibrosis-related Diseasesmentioning
confidence: 99%
See 3 more Smart Citations